Creatine supplementation associated with strength training trained in men - Corrêa, Daniel Alves (2013)
Ergogenic resources are being consumed more frequently in gyms due to its purpose of providing income in certain physical activity since competitive and aesthetic purposes, the increase in muscle strength and hypertrophy of one most desired goals among practitioners of strength training. Creatine becomes a supplement widely used in strength training, where individuals do intake during training protocols, in order to gain strength, power and muscle hypertrophy. The aim of this review is to investigate the use of creatine supplementation combined with strength training, the use actually contribute to expected results in increased strength and hypertrophy in men trained individuals with experience in strength training and does not bring adverse results to the body with the use of creatine. Therefore, we conclude that creatine supplementation combined with strength training collaborated on improvements in increasing muscle strength and hypertrophy is considered a safe practice.